Construction of Women in Religious Relations and Social Change on The Indonesia-Singapore Border, Batam City, Riau Islands - Emmy Solina; Nikodemus Niko; Marisa Elsera (Ideas Publishing, 2023)
This study explores the construction of women in religious relations and their role in social change on the Indonesia-Singapore border, specifically focusing on Batam City in the Riau Islands. The religious landscape of this region is diverse, with various religious practices and beliefs coexisting. Understanding the dynamics of gender within these religious contexts is crucial to comprehending how women navigate and contribute to social change. The research employs a qualitative approach, such as observation, interviews, and document analysis. By engaging with local communities, religious leaders, and women themselves, this study seeks to uncover the multifaceted roles women play within religious institutions and the broader society. The findings shed light on the ways in which women negotiate their religious identities, practices, and responsibilities, as well as the challenges they encounter in their pursuit of social change. The study also examines the impact of globalization and transnational connections on the construction of women's religious roles, exploring how women in Batam City are influenced by and respond to global trends and ideas. Furthermore, the research addresses the power dynamics at play within religious institutions and how they shape women's experiences and opportunities for social transformation. It investigates the agency exercised by women in religious leadership roles and grassroots initiatives, highlighting the strategies they employ to challenge existing gender norms and advocate for gender equality.